COLTRIMS Experiments on State-Selective Electron Capture in Alpha-He Collisions at Intermediate Energies - Alessi, Mariana; Otranto, Sebastián; Focke, Pedro Rodolfo (World Scientific, 2012)
Fil: Alessi, Mariana. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina